QTL mapping for yield traits in vegetable cowpea - Ashwin V Varghese (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2017)
Cowpea [Vigna unguiculata (L.) Walp.] is one of the most cultivated pulse crops in the semi-arid tropics of Asia, Africa, Southern Europe, and other parts of the world. It is used for both vegetable and fodder purpose. In India, kharif crop of vegetable cowpea is cultivated in an estimated area of 0.5 million hectares in states like Kerala, Karnataka, Tamil Nadu and Madhya Pradesh. Studies aimed at increased yield among crops were always challenged by the quantitative nature of traits. These quantitative traits are generally governed by multiple genes present in regions of the genome called quantitative trait loci (QTL). With the advent of molecular markers it is possible to localize the QTL with the help of linked markers, a process now widely known as QTL mapping. QTL mapping depicts the relative positioning of different markers on the chromosomes and their linkage to a specific trait. In cowpea, even though there has been few mapping efforts for traits such as resistance to Thrips tabaci and Frankliniella schultzei, flowering time, pod length and seed weight, an elaborate QTL map for yield and related traits is missing. Hence, the study “QTL mapping for yield traits in vegetable cowpea” was undertaken with the objective of mapping the SSR markers and identifying the quantitative trait loci for yield components in the genome of vegetable cowpea at the Centre for Plant Biotechnology and Molecular Biology (CPBMB), College of Horticulture, during February 2016 to June 2017. F3 plants maintained at CPBMB, derived from the cross of Sharika which is a pole type, long poded, high yielding but anthracnose and cowpea mosaic virus susceptible cultivar with Kanakamony which is a semi-trailing, medium-long poded, low yielding, anthracnose immune and cow pea mosaic virus resistant cultivar, were used to raise the F4 mapping population. Morphological observation for traits pod length, individual pod weight (IPW), pod number, days taken for first flowering (DTFF), total dry pod yield (TDPY), grains per pod, branch number, root length, plant height, plant weight, and response to anthracnose and cowpea mosaic virus diseases were recorded. High quality DNA was isolated from the parents and mapping population using the protocol standardized in this study. One hundred SSR primer pairs reported in cowpea were screened among the parental DNA for polymorphism. Thirty polymorphic primer sets were carried forward to genotype the F4 mapping population. The morphological and genotypic data were used to construct a linkage map using software ICIMapping. Two linkage groups, one having eight SSR markers distributed across 637 cM and another one having five SSR markers distributed across 271 cM were obtained. Two approaches, Single Marker Analysis (SMA) and Inclusive Composite Interval Mapping (ICIM) otherwise called Additive Linkage Mapping were followed for QTL mapping. LOD value threshold of 3.0 was used to determine the significance of QTL and linked markers. Multiple QTL hotspots were observed for different traits under study. An anchored marker, CLM0083 has been identified which was significantly linked to traits individual pod weight and total dry pod yield. The region between 25 cM to 125 cM on linkage group 1 had QTL hotspots harboring genes governing traits DTFF, TDPY, root length, plant length and plant height. This entire region was bracketed by two markers, CLM0244 at 24.25 cM and CLM0177 at 126.86 cM with an anchored marker CLM0008. This marker combination could be potentially used in marker assisted selection for the traits DTFF, TDPY, root length, plant length and plant height. Fine mapping of the QTL for these traits with large number of markers would provide more insights into the genes and hot spots involved in the yield contributing traits in cowpea.